Smart Grids: benefícios de uma rede elétrica inteligente - COSTA, Erick Melonio da (2018)
The present work has as object of study of smart grids in Brazil, presenting them as a set of technologies that will revolutionize the energy sector in several aspects, as operation, pricing models, consumption patterns, services, and also presenting consumer applications such as electricity supplier. These changes bring about a remake of the set of rules governing the electricity sector for the current analysis of the limits and possibilities posed by the current regulatory instruments. There is an opportunity for restructuring the essential core of the electricity services in reference to the postulate of the centrality of the individual in the adoption of consumption patterns and definitions of energy policy. Thus, we discuss the formulation of regulations for the smart grid, the light, in particular: the rational use of energy resources, the search for the appropriate service, the new horizon for distributed generation, the new distribution of roles and convergence infrastructure that approximates the energy services and telecommunications.